1991
DOI: 10.1080/02678299108036423
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Columnar.cis, cis-(3,5-dihydroxycyclohexyl)-3,4,5-tris(alkoxy)benzoates Thermal behaviour and water absorption

Abstract: The thermal behaviour of freeze dried and water saturated samples of a homologous series of hexagonal columnar, liquid-crystalline cis,cis-(3,5-dihydroxycyclohexyl)-3,4,5-tris(alkoxy)benzoates (three chain diols) is discussed. The water absorption from a saturated atmosphere as well as in direct contact is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Increasing the number of aliphatic chains grafted to a rigid core or even to a nonanisometric but distinct polar molecular part leads to an increase in the volume fraction of the lipophilic aliphatic region. Nonlamellar mesophases such as columnar or cubic can result, as has been successfully demonstrated, e.g., for polycatenar and swallow-tailed mesogens, for taper-shaped polyhydroxy amphipiles, , and for cone-shaped dendrimers …”
Section: Introductionmentioning
confidence: 75%
“…Increasing the number of aliphatic chains grafted to a rigid core or even to a nonanisometric but distinct polar molecular part leads to an increase in the volume fraction of the lipophilic aliphatic region. Nonlamellar mesophases such as columnar or cubic can result, as has been successfully demonstrated, e.g., for polycatenar and swallow-tailed mesogens, for taper-shaped polyhydroxy amphipiles, , and for cone-shaped dendrimers …”
Section: Introductionmentioning
confidence: 75%
“…Ordered discotic networks with stabilized Φ mesophases using cross-linkable chain ends have also been reported . Recent work has shown that some nondisk molecules can be self-assembled into Φ phases. Columnar phase formation in numerous LC polymers with rodlike mesogens has also been reported. …”
Section: Introductionmentioning
confidence: 98%
“…Disklike molecules intrinsically possess a flat, rigid, and rotationally symmetric core connected with flexible tails. The core structures are commonly constructed by a single phenylene group, , several phenylene groups, metal ion complexes, or self-assembled disk-shaped systems. The flexible tails, which are alkyl chains in most cases, sometimes bearing functional end groups, are necessary to form discotic LC phases.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly of discotic molecules consisting of a disk-shaped aromatic core and peripheral flexible side chains occurs through microsegregation between the aromatic core and the peripheral chains in bulk or in organic solvents. Noncovalent interactions such as π−π interactions, hydrogen bondings, and solvophobic effects are the main driving forces for the microsegregation.…”
Section: Introductionmentioning
confidence: 99%